2019
DOI: 10.1371/journal.pgen.1008164
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of multisite chronic pain in UK Biobank

Abstract: Chronic pain is highly prevalent worldwide and represents a significant socioeconomic and public health burden. Several aspects of chronic pain, for example back pain and a severity-related phenotype ‘chronic pain grade’, have been shown previously to be complex heritable traits with a polygenic component. Additional pain-related phenotypes capturing aspects of an individual’s overall sensitivity to experiencing and reporting chronic pain have also been suggested as a focus for investigation. We made use of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
226
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(254 citation statements)
references
References 138 publications
25
226
3
Order By: Relevance
“…In line with a recent GWAS on multisite chronic pain [36] and other studies [58,82], we found that depression (including major depressive disorder) and anxiety may increase the risk of CP. This finding is important as so far, studies have been conflicting with regard to whether depression increase the risk of pain or vice versa [13,24,32,35,70,82].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with a recent GWAS on multisite chronic pain [36] and other studies [58,82], we found that depression (including major depressive disorder) and anxiety may increase the risk of CP. This finding is important as so far, studies have been conflicting with regard to whether depression increase the risk of pain or vice versa [13,24,32,35,70,82].…”
Section: Discussionsupporting
confidence: 91%
“…Using Complex Traits Genetics Virtual Lab (CTG-VL) [18], we explored whether those SNPs have been previously associated to other traits. We observed that rs10660361 was also identified by a recent GWAS on back pain (P-value = 7.77×10 −8 ) [25] and multisite chronic pain (P-value = 1.9×10 −9 ) [36]. However, rs113313884 was only associated with multisite chronic pain at a suggestive level (P-value = 6.9×10 −3 ) highlighting the importance of studying phenotypes using different definitions.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations